The Streaming Paradox: Untangling the Hybrid Gatekeeping Mechanisms of Music Streaming. - Maasø, Arnt; Spilker, Hendrik Storstein (Popular Music & Society, 2022)
Why does music listening in streaming services seem tied to a superstar economy despite the plenitude of digital music? This article explores what we label the streaming paradox: the way in which plenitude at the outset produces narrowness as the outcome. Based on dissection of the interfaces of streaming services, interviews with stakeholders, and analyses of user data, the article introduces six key gatekeeping mechanisms (and concepts) at work in the platforms. These mechanisms are combined effects of algorithmic coding, interface design, and human curation and choices and serve as explanations for the streaming paradox.